"Institutionalization Aversion" and the Willingness to Pay for Home Health Care - Joan Costa-i-Font (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine the presence of a systematic preference for independent living at old age which we refer as “institutionalization aversion” (IA). Given that IA is not observable from revealed preferences, we draw on a survey experiment to elicit individuals' willingness to pay (WTP) to avoid institutionalization (e.g., in a nursing home), using a double-bounded referendum WTP format. Our results suggest robust evidence of IA and reveal a willingness to pay of up to 16% of respondent's (individuals over fifty-five years of age) average income. We find that estimates of the willingness to pay to avoid institutionalization (or exteuro292 at the time of the study) exceed the amount respondents are willing to pay for home health care at old age in the event of a mild impairment ( exteuro222). WTP estimates vary with income, age and especially, respondents' housing conditions. Finally, we test the sensitivity of our estimates to anchoring effects and `yea-saying' biases.
Keywords: R21; I18; 330; institutionalisation aversion; state-dependent preferences; home health care; willingness to pay; caregiving; referendum format